2016
DOI: 10.1002/jnr.23900
|View full text |Cite
|
Sign up to set email alerts
|

Heterogeneity in oligodendroglia: Is it relevant to mouse models and human disease?

Abstract: There are many lines of evidence indicating that OPC and oligodendrocyte populations in the CNS are heterogeneous based on their developmental origins as well as from morphological and molecular criteria. Whether these distinctions reflect functional heterogeneity is less clear and has been the subject of considerable debate. Recent findings particularly from knockout mouse models have provided new evidence for regional variations in myelination phenotypes, particularly between brain and spinal cord. These dat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
13
0

Year Published

2017
2017
2019
2019

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(17 citation statements)
references
References 142 publications
(154 reference statements)
3
13
0
Order By: Relevance
“…Comparison of the findings for BLA (EC, BLA, IC, CeA) and CeA (IC, CeA) suggests that CeA oligodendrocytes are more sensitive to CSS; the IC white matter tract, which contains axon projections to GABA neurons in medial intercalated cell masses, might be particularly stress sensitive. This variation between ROIs concurs with the proposal that oligodendrocyte function, including gene expression levels, varies between brain regions …”
Section: Discussionsupporting
confidence: 90%
“…Comparison of the findings for BLA (EC, BLA, IC, CeA) and CeA (IC, CeA) suggests that CeA oligodendrocytes are more sensitive to CSS; the IC white matter tract, which contains axon projections to GABA neurons in medial intercalated cell masses, might be particularly stress sensitive. This variation between ROIs concurs with the proposal that oligodendrocyte function, including gene expression levels, varies between brain regions …”
Section: Discussionsupporting
confidence: 90%
“…The lack of a strong phenotype in Polr3a KI/KI and KI/KO mice could potentially be explained by the much higher proportion of white matter in the human brain (more than 50%) compared to other species (around 10% in mouse) [4143]. This might make the human brain more vulnerable than the mouse brain to mutations in genes important for myelination.…”
Section: Discussionmentioning
confidence: 99%
“…As described in Section 2, during development, OPCs arise from different brain areas. This raises the question whether OPCs from different origins represent specific OPC subpopulations with distinct functional features (Ornelas et al, ). Kessaris et al () revealed that OPCs derived from the three successive waves depicted in Figure are characterized by different transcription factors.…”
Section: Opc Heterogeneitymentioning
confidence: 99%